1H-NMR-based metabolic profiling identifies non-invasive diagnostic and predictive urinary fingerprints in 5q spinal muscular atrophy - Saffari, Afshin; Cannet, Claire; Blaschek, Astrid; Hahn, Andreas; Hoffmann, Georg F.; Johannsen, Jessika; Kirsten, Romy; Kockaya, Musa; Kölker, Stefan; Müller-Felber, Wolfgang; Roos, Andreas; Schäfer, Hartmut; et al. (Orphanet journal of rare diseases, 2021)
5q spinal muscular atrophy (SMA) is a disabling and life-limiting neuromuscular disease. In recent years, novel therapies have shown to improve clinical outcomes. Yet, the absence of reliable biomarkers renders clinical assessment and prognosis of possibly already affected newborns with a positive newborn screening result for SMA imprecise and difficult. Therapeutic decisions and stratification of individualized therapies remain challenging, especially in symptomatic children. The aim of this proof-of-concept and feasibility study was to explore the value of 1H-nuclear magnetic resonance (NMR)-based metabolic profiling in identifying non-invasive diagnostic and prognostic urinary fingerprints in children and adolescents with SMA.
Im Text ist "1" hochgestellt
Gesehen am 15.01.2022